Handbook of Africa?s international relations - Murithi, Timothy (London Routledge, 2014)
"Analyses current themes in Africa?s international relations. Discusses the growing prominence of the African continent on the world stage, the evolution of Pan-Africanism and the emerging role of the African Union as an international actor"
Includes bibliographical references and index.
Keywords: African Union